(untitled) (Scientific journal of the Fergana State University, 2023)
This article shows the importance of gastronomic tourism, its place in the tourism infrastructure today, the share of income from this sector in our economy, at the same time, the high level of gastronomic tourism in the Republic of Uzbekistan is shown, it is shown on the example of each province, and the differences and connections between the provinces are analyzed. Several proposals for the development of gastronomic tourism have been made.